The genus Hexopetion Burret (Arecaceae) - Pintaud, Jean-Christophe (2008)
The genus Hexopetion was described by Burret to accommodate a single species, H. mexicanum. We reinstate the genus on the basis of morphological and anatomical data, and enlarge it to include a second species, Astrocaryum alatum, for which a new combination is made.